The Current State and Development Trends of Marketing Management in Higher Education Institutions - Shodiyabonu Abitdjanovna Khodjayeva (Scientific Trends, 2025)
The article analyzes the current modern state of marketing management in higher education institutions, its development trends, and international experience. Through marketing approaches, the processes of building the brand of educational institutions, increasing competitiveness, creating student-oriented services, and digital transformation are highlighted. Based on international statistics and Uzbekistan’s experience, conclusions are developed on improving marketing management in the higher education system.